Evaluation of antibacterial activity of Lavandula stoechas L. essential oil - K Kavya, M C Gayatri, U Sudha, J Shubha, (Journal of Spices and Aromatic Crops, 2013)
The antibacterial activity of crude and essential oil extract of Lavandula (Lavandula stoechas) against the infectious bacteria viz., Escherichia coli, Bacillus subtilis, Pseudomonas spp. and Staphylococcus aureus were evaluated in vitro. It was found that L. stoechas oil exhibits high antibacterial activity against S. aureus, Pseudomonas spp, B. subtilis and E. coli when compared to crude extract. The in vitro Minimum Inhibitory Concentration (MIC) of L. stoechas oil was found to be 50 μg mL-1 for inhibiting the growth of B. subtilis and S. aureus whereas, it was found to be 25 μg mL-1 for E. coli and Pseudomonas spp. The statistical analysis for MIC of L. stoechas oil was found to be 42.82 μg mL-1 for inhibiting the growth of B. subtilis and S. aureus where it was found to be 22.25 μg m-1 for E. coli and Pseudomonas spp.